PENINGKATAN PENDAPATAN PETANI DI RAWA LEBAK MELALUI PENGANEKARAGAMAN KOMODITAS - Suparwoto, Suparwoto; Waluyo, Waluyo (Publikasi Penelitian Terapan dan Kebijakan, 2009)
Swampland has function which significant to human being prosperity. Generally be exploited for the agricultural activity, ranch and fishery. Peasant plant paddy only once in a year, afterwards it is not cultivated again ( blush). If happened attack of mouse pest, flooded and dryness hence will result the failure harvest. They can overcome with cultivation of various commodity type to support improvement of peasant income. Result of research indicate that at superficial swampland and middle swampy can cultivated by rice/palawija/horticulture, deep swampland can cultivated by rice/fish and in lawn afforded by livestock of bird and ruminant population. With improvement of intensity cropping in swampland hence have an effect on to improvement of peasant income. The objective to give information in improving peasant income by affording various commodity type in swampland.